FunMaths / Teh Sok Hoon - Teh, Sok Hoon (2003)
Over the past two decades electronic game have become ingrained in our culture Children's fixation with these games initially alarmed parents and educators, but educational researchers soon questioned whether the motivation to play could be tapped and harnessed for educational purposes. A number of educational electronic games have been developed and theory success has been mixed. Thus, I have chosen my thesis title as " Interactive Multimedia Educational Game" which we have name it as Kids Heaven and I will develop an educational gamer for mathematics which I name it as FunMaths while my partner will be doing about Science, FunScience. This Game was created in CD-Rom based and will be suitable for students in primary school especially age between 7 and 12, parents and teacher and will only include questions based on Mathematics operations for not more than three digits. Users will be able to choose the level of difficulties. One of the objectives of this game is to help teachers in teaching mathematics in English and to help the students to understand more about the subject. The system implements the concepts of multimedia, which integrates text, graphics, animations and audio into the game display to make the game more attractive especially for the kids. Macromedia Author ware 6, Macromedia Flash MX, Adobe Photoshop 6.0 and some other tools was used to develop the interactive game. Finally, I hope the "Multimedia Interactive Educational Game" can serve to enable players enjoy themselves throughout the playing and learning process, and to achieve the objective specified before the system is develop.